A rubric to assess opportunities for research engagement in the policy process - Ratner, Blake D.; Dubois, Mark (International Food Policy Research Institute, 2022)
Figure 1. A rubric to assess opportunities for research engagement in the policy process. Examples in the table are illustrative of possible modes of engagement. Source: Ratner, B & Dubois, M. et al 2022.